2015
DOI: 10.1155/2015/319240
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal and Antibacterial Metabolites from a French Poplar Type Propolis

Abstract: During this study, the in vitro antifungal and antibacterial activities of different extracts (aqueous and organic) obtained from a French propolis batch were evaluated. Antifungal activity was evaluated by broth microdilution on three pathogenic strains: Candida albicans, C. glabrata, and Aspergillus fumigatus. Antibacterial activity was assayed using agar dilution method on 36 Gram-negative and Gram-positive strains including Staphylococcus aureus. Organic extracts showed a significant antifungal activity ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 55 publications
6
50
0
Order By: Relevance
“…Caffeic acid (5), p-coumaric acid (6), ferulic acid (7) and isoferulic acid (14) were also detected in those propolis samples. The study of Chasset et al [42] was in concordance with [40,41] finding about the composition of French propolis, where they investigated propolis from different areas in France through high-performance thin-layer chromatography and mass spectrometry (HPTLC/MS). Regardless the collection area of propolis in France, phenolic acids and flavonoids predominated in the extracts.…”
Section: Southern European Coastsupporting
confidence: 61%
See 3 more Smart Citations
“…Caffeic acid (5), p-coumaric acid (6), ferulic acid (7) and isoferulic acid (14) were also detected in those propolis samples. The study of Chasset et al [42] was in concordance with [40,41] finding about the composition of French propolis, where they investigated propolis from different areas in France through high-performance thin-layer chromatography and mass spectrometry (HPTLC/MS). Regardless the collection area of propolis in France, phenolic acids and flavonoids predominated in the extracts.…”
Section: Southern European Coastsupporting
confidence: 61%
“…[140,162,163] Benzyl caffeate, p-coumaric acid and pinocembrin were predominant in French propolis sample and showed a great effectiveness against tested pathogens exhibiting an important antibacterial and antifungal activities against Staphylococcus aureus; Escherichia coli, and Candida albicans. [164] More recently, Boisard et al [41] have found the same properties of aqueous and methanolic extracts of poplar propolis, where they found a selective Gram-positive antibacterial activity, in particular against Staphylococcus aureus and several of its methicillin-resistant (MRSA) and methicillin-susceptible (MSSA) strains. [41] Moreover, Amoros et al [165] have shown that 80 % ethanol extract of propolis from Renne, France, possess an antiviral effect against Herpes simplex virus (HSV-1).…”
Section: Antimicrobial Activity Southern European Coastmentioning
confidence: 90%
See 2 more Smart Citations
“…As examples: Boisard et al [17] found that the flavonoids pinobanksin-3-acetate, pinocembrin, chrysin, and galangin did not show anti-MRSA activity, in contrast to the prenyl caffeate. Nevertheless, the activities of the extracts were higher than the isolated compounds, which evidence a synergetic activity among the compounds present in the extracts.…”
Section: Discussionmentioning
confidence: 99%